Estimates of use of preferred contraceptive method in the United States: a population-based studyResearch in context - Anu Manchikanti Gomez; Ariana H. Bennett; Jennet Arcara; Lisa Stern; Jamie Bardwell; Denicia Cadena; Aisha Chaudhri; Laura Davis; Christine Dehlendorf; Brittni Frederiksen; Catherine Labiran; Raegan McDonald-Mosley; et al. (Elsevier, 2024)
Summary: Background: In the U.S. and globally, dominant metrics of contraceptive access focus on the use of certain contraceptive methods and do not address self-defined need for contraception; therefore, these metrics fail to attend to person-centeredness, a key component of healthcare quality. This study addresses this gap by presenting new data from the U.S. on preferred contraceptive method use, a person-centered contraceptive access indicator. Additionally, we examine the association between key aspects of person-centered healthcare access and preferred contraceptive method use. Methods: We fielded a nationally representative survey in the U.S. in English and Spanish in 2022, surveying non-sterile 15-44-year-olds assigned female sex at birth. Among current and prospective contraceptive users (unweighted n = 2119), we describe preferred method use, reasons for non-use, and differences in preferred method use by sociodemographic characteristics. We conduct logistic regression analyses examining the association between four aspects of person-centered healthcare access and preferred contraceptive method use. Findings: A quarter (25.2%) of current and prospective users reported there was another method they would like to use, with oral contraception and vasectomy most selected. Reasons for non-use of preferred contraception included side effects (28.8%), sex-related reasons (25.1%), logistics/knowledge barriers (18.6%), safety concerns (18.3%), and cost (17.6%). In adjusted logistic regression analyses, respondents who felt they had enough information to choose appropriate contraception (Adjusted Odds Ratio [AOR] 3.31; 95% CI 2.10, 5.21), were very (AOR 9.24; 95% CI 4.29, 19.91) or somewhat confident (AOR 3.78; 95% CI 1.76, 8.12) they could obtain desired contraception, had received person-centered contraceptive counseling (AOR 1.72; 95% CI 1.33, 2.23), and had not experienced discrimination in family planning settings (AOR 1.58; 95% CI 1.13, 2.20) had increased odds of preferred contraceptive method use. Interpretation: An estimated 8.1 million individuals in the U.S. are not using a preferred contraceptive method. Interventions should focus on holistic, person-centered contraceptive access, given the implications of information, self-efficacy, and discriminatory care for preferred method use. Funding: Arnold Ventures.